Microscopy and microanalysis of zinc-magnesium alloys related to their microhardness and electrochemical behavior in koh solution - Sankum Nusen (2018)
© 2018 Trans Tech Publications, Switzerland. Zn-Mg alloys containing up to 5.28 wt.%Mg were prepared by gravity casting. Light and scanning electron microscopy with energy-dispersive X-ray spectrometry were used to characterize their as-cast microstructure as compared to that of pure zinc. The alloy with 3.60 wt.%Mg was found to be eutectic. Phase identification by X-ray diffractometry suggested that the eutectic Mg-rich phase wasMg2 Zn11 with two types of intermetallic compounds, including Mg2 Zn11 and MgZn2, present in the alloy with 5.28 wt.%Mg. The microhardness increased with increasing Mg content from 41 HV for pure zinc to 266 HV for the alloy with 5.28 wt.%Mg. The electrochemical behavior of the alloys was studied by potentiodynamic polarization test at room temperature using 8.5 M KOH solution as electrolyte. Hydrogen evolution was generally postponed for the cases of Zn-Mg alloys as compared to pure zinc. The corrosion potential (Ecorr) was not significantly affected by Mg addition into Zn, while the corrosion current density (icorr) was significantly increased, especially for the case of the alloy with 3.60 wt.%Mg, as compared to that of pure zinc. It can be proposed that, due to its relatively higher hydrogen overpotential and uniform corrosion in KOH solution, the eutectic alloy with 3.60 wt.%Mg can be an alternative to pure zinc for use as anode in applications related to alkaline electrolyte.